Правові питання планування земель в умовах децентралізації влади - Ущаповська, О.; Uschapovska, O. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглянуто науково-теоретичні і практичні аспекти планування земель в умовах реформування державного регулювання земельних відносин на засадах децентралізації влади і розширення функцій та повноважень органів місцевого самоврядування у сфері земельних відносин на території громад. After the adoption of the Land Code of Ukraine on October 25, 2001, the state authorities centralized such functions of state administration and regulation in the sphere of land use and protection, such as planning of territories, land management, disposal of state-owned land outside the boundaries of settlements, restricted land jurisdiction of local self-government bodies by village boundaries , towns, cities, in consequence of that land in public relations experience such negative phenomena as corruption, raiding and other unlawful phenomena that need to be overcome. The Land reform can’t be completed without solving a set of organizational and legal issues regarding the improvement of the planning system in the sphere of land ownership relations, the use and protection of land, the state regulation of land relations in the context of decentralization of power and the expansion of the powers of local government bodies in the sphere of land relations. In this regard, it would be advisable to revise the system and structure of the current land legislation in order to bring it in line with the legislation on territorial planning, environmental and other legislation regarding the implementation by the state and local government authorities of land use planning in conditions of decentralization of power.
Legal Issues of Land Planning in Conditions of Decentralization of Power
Keywords: планування земель; земля; регулювання земельних відносин; децентралізація влади; територіальні громади; land planning; land; regulation of land relations; decentralization of power; territorial communities